PECULIARITIES OF AUDITORY PERCEPTION OF INTONATION OF INTEROGATIVES IN THEATRICAL PUBLIC PERFORMANCE AS A KIND OF DRAMATIC MONOLOGUE - Lyssenko , Catherine (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article deals with specific features of perception of public speaking prosody. Speech intonation is an important component of oral text, a carrier of semantic meanings, and at the same time a means of demonstrating the emotionally expressive nature of expression. The nature and influence of public speaking depends not only on the adequately disclosed facts, but also on the very speech form of their presentation. The leading role in this process belongs to prosodic means, in which the peculiarities of public broadcasting are clearly revealed. The article examines the interrogatives of quasi-spontaneous public speakingmonologues from Shakespeare's plays, gathered from audio recordings of different periods of time, dating back to 30 years of the last century. This approach made it possible to compare the main features of interrogative rhetorical questions in the chronological plan. In the analysis of prosodic features of question structures, the inventory of their universal characteristics was distinguished, since there are certain normative, invariant prosodic models for the main types of questions. On the other hand, the melody should be attributed to the most variable parameters of interoactive constructions, so the most typical variants of intonational deviations were also analyzed.__________Література:• Беличенко, Л. Г. «Роль и место просодии в системе средств речевого воздействия (экспериментально-фонетическое исследование на материале английских публицистических текстов политического характера).» Автореф. дис. канд. филол. наук (Москва, 1990).• Вербич, Н. С. «Інтонація переконування в публічному мовленні (експериментально-фонетичне дослідження).» Автореф. дис. канд. філол. наук (Київ, 2007).• Георгієва, Н.Ю. «Просодія переконування в англійському діалогічному мовленні (експериментально-фонетичне дослідження).» Автореф. дис. канд. філол. наук (Одеса, 2005).• Красильникова, Е.М. «Просодическая реализация функции воздействия в текстах информационного и ораторского сталей: на материале американского варианта английского языка.» (Дис. канд. филол. наук, Волгоград, 2005),• Склярова, С. Н. Влияние речевой тональности на эволюцию интонационального строя языка (экпериментально-фонетическое исследование на материале английского, немецкого и руского языков) (Пятигорск, 2009), 118.